STRATEGI KOMUNIKASI DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN SIAK DALAM MENGIMPLEMENTASIKAN PROGRAM SEKOLAH RAMAH ANAK - Cici Ramadhanty; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The Siak Regency Education and Culture Office is cooperating with the Women's Empowerment Office for Child Protection in Population and Family Planning (DP3AP2KB) in order to make Siak Regency a Child-Friendly Regency through the Child Friendly School program. The purpose of this study was to determine the communication strategy of the Office of Education and Culture of Siak Regency in implementing the Child Friendly School program. This research uses descriptive qualitative research methods. Data collection techniques used in this study were interviews, observation, and documentation. The informants involved in this study amounted to 7 people who were determined based on a purposive technique. Data analysis techniques were carried out using the interactive data analysis model of Miles and Huberman by using data validity checking techniques, namely triangulation and extension of participation. The results of this study indicate that in implementing Child Friendly Schools, the Office of Education and Culture of Siak Regency using communication strategies include the determination of communicator strategies in which the Office of Education and Culture of Siak Regency has appointed the Head of Early Childhood Education and Education Development, Head of Elementary Development Division, and Head of Middle School Development Division as communicators. The target audience of the Office of Education and Culture of Siak Regency is children and parents as primary audiences and all school residents and the community as secondary audiences. Furthermore, in the message management strategy, the core message delivered is about the concept of child-friendly schools in accordance with existing indicators from the ministry. The method used in conveying messages is an educative method, persuasive methods and repeating reminders repeatedly to SRA message schools and holding coaching to schools every month. The media used are Whatsapp social media, print media and online media. Keyword: Communication Strategy, Child Friendly School, Siak Regency Education and Culture Office